Comparative proteomics lends insight into genotype‐specific pathogenicity. Issue 17 (2nd September 2013) - Guarnieri, Michael T.
<x xml:space="preserve">Abstract</x> Comparative proteomic analyses have emerged as a powerful tool for the identification of unique biomarkers and mechanisms of pathogenesis. In this issue of Proteomics, Murugaiyan et al. utilize difference gel electrophoresis (DIGE) to examine differential protein expression between nonpathogenic and pathogenic genotypes of Prototheca zopfii, a causative agent in bovine enteritis and mastitis. Their findings provide insights into molecular mechanisms of infection and evolutionary adaptation of pathogenic genotypes, demonstrating the power of comparative proteomic analyses.